Aflatoxin B1 induces the transversion of G-->T in codon 249 of the p53 tumor suppressor gene in human hepatocytes. - Aguilar, F (1993)
Approximately half of hepatocellular carcinoma (HCC) from regions in the world with high contamination of food with the mycotoxin aflatoxin B1 (AFB1) contain a mutation in codon 249 of the p53 tumor suppressor gene. The mutation almost exclusively consists of a G-->T transversion in the third position of this codon, resulting in the insertion of serine at position 249 in the mutant protein. To gain insight into the mechanism of formation of this striking mutational hot spot in hepatocarcinogenesis, we studied the mutagenesis of codons 247-250 of p53 by rat liver microsome-activated AFB1 in human HCC cells HepG2 by restriction fragment length polymorphism/polymerase chain reaction genotypic analysis. AFB1 preferentially induced the transversion of G-->T in the third position of codon 249. However, AFB1 also induced G-->T and C-->A transversions into adjacent codons, albeit at lower frequencies. Since the latter mutations are not observed in HCC it follows that both mutability on the DNA level and altered function of the mutant serine 249 p53 protein are responsible for the observed mutational hot spot in p53 in HCC from AFB1-contaminated areas. Our results are in agreement with an etiological role of AFB1 in hepatocarcinogenesis in regions of the world with AFB1-contaminated food.